Skrif en kerkorde - A. Celliers; P. J. Strauss (Acta Theologica)
The church is continuously called upon to listen to the Word of God so that, under the guidance of the Holy Spirit, it can remain church in and for its time, as God intended it to be. The Word  presents a unique, complex, and multifaceted image of the church. This reflects the dynamic way in which the Lord enables His church to be church in its specific circumstances. This multifaceted image of the church elicits certain constants that form the outlines of the nature and order of the church. As far as the organisational aspects are concerned, it is important to realise that Jesus Christ is the structure of the church, and that He sees to it that it is being served in an orderly fashion. Every member has a God-given responsibility within the church, and existing ministries have  the responsibility to instruct the congregation in the teaching of the gospel in particular. This enables the congregation to adhere to its calling for obedience, love, and witness, so that the church  can continue to exist. The outlines of the nature and order of the church should be addressed in all church orders to avoid pragmatism and arbitrariness on the one hand, and to create space for the various demands of local circumstances on the other.